Bismuth‐Based Perovskite‐Inspired Solar Cells: In Situ Diagnostics Reveal Similarities and Differences in the Film Formation of Bismuth‐ and Lead‐Based Films. Issue 7 (12th May 2019) - Tang, Ming-Chun; Barrit, Dounya; Munir, Rahim; Li, Ruipeng; Barbé, Jérémy M.; Smilgies, Detlef-M.; Del Gobbo, Silvano; Anthopoulos, Thomas D.; Amassian, Aram
Abstract : Organic–inorganic lead‐based halide perovskite compounds currently yield thin film solar cells with a power conversion efficiency (PCE) of >23%. However, replacing the lead with less‐toxic elements while maintaining a high PCE remains a challenge. For this reason, there has been significant effort to develop Pb‐free compounds, including methylammonium bismuth iodide (MA3 Bi2 I9 ), but such systems severely underperform when compared with the prototypical Pb‐based methylammonium lead iodide (MAPbI3 ). For the latter, it is known that lead complexes with polar solvents, such as dimethyl sulfoxide (DMSO) and dimethylformamide (DMF), to form iodoplumbates which can co‐crystallize into solvated phases. Herein, the solidification and growth behaviors of Bi‐ and Pb‐based films is investigated using multi‐probe in situ characterization methods. It is shown that the Bi‐based compound crystallizes directly and rapidly into a textured polycrystalline microstructure from a precursor solution without evolving through intermediate crystalline solvated phases, in contrast to MAPbI3 . This solidification process produces isolated crystals and challenges the growth of continuous and crystalline films required for solar cells. It is revealed that solvent engineering with antisolvent dripping is crucial to enable the formation of continuous polycrystalline films of MA3 Bi2 I9 and functional solar cells thereof. Abstract : Formation of lead‐free methylammonium bismuth iodide (MA3 Bi2 I9 ) films is investigated in situ by X‐ray scattering and optical spectroscopy and contrasted to methylammonium lead iodide (MAPbI3 ). The Bi‐based compound crystallizes directly from solution, whereas the Pb‐based perovskite initially forms a solvated crystalline phase requiring annealing for conversion. Both materials benefit from anti‐solvent dripping while the as‐cast film is in the disordered sol–gel state.